(untitled) (Academia Journal of Medicine, 2024)
Background: To evaluate the effectiveness of Teneligliptin as an add-on therapy in type 2 diabetes mellitus (T2DM) patients inadequately controlled with a stable dose of Metformin and Glimipride. Subjects and Methods: Pateints with type II DM on Metformin 1-2gm per day and Glimipride 1-4mg per day were prescribed with TENELIGLIPTIN 20mg tablet once daily. The patients Were followed up in OPD every month till 3 months. At the end of 3 months, Blood Pressure, Body weight CBC,KFT,LFT, Lipid Profile, Fasting Blood sugar, 2 hours Post parandial Blood sugar and HbA1c was assessed. The difference in all the mentioned parameters was used to determine the effectiveness of TENELIGLIPTIN. Result: There were more males as compared to females. Mean age among the study subjects was 59.08±12.17 years Family history of diabetes was revealed in 34.17% of the subjects.48.33% of the subjects had diabetes since 5-10 years. Hypertension and cardiovascular disease was revealed in 14.17% and 6.67% of the subjects respectively. After intervention, mean weight among study subjects reduced to 71.97 from 72.61. After intervention; HbA1c, FBS and PPBS reduced to 7.02±0.44, 131.70±6.17 and 204.95±9.39 Mean Triglyceride, HDL, LDL and VLDL among the study subjects was 151.76±6.19, 38.28±2.87, 108.11±6.43 and 39.32±3.12 among the study subjects. Conclusion: The present assessment shows patients with T2DM who were treated with teneligliptin had measurably large and clinical important reductions in HbA1c levels.